A Rigidity Result for Overdetermined Elliptic Problems in the Plane. Issue 7 (22nd April 2017) - Ros, Antonio; Ruiz, David; Sicbaldi, Pieralberto
Abstract : Let f : [ 0, + ∞ ) → ℝ be a (locally) Lipschitz function and Ω ⊂ ℝ 2 a C 1, α domain whose boundary is unbounded and connected. If there exists a positive bounded solution to the overdetermined elliptic problem [ Δ u + f ( u ) = 0 in Ω